1994
DOI: 10.1007/bf00284204
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila GABAergic systems II. Mutational analysis of chromosomal segment 64AB, a region containing the glutamic acid decarboxylase gene

Abstract: The Drosophila melanogaster Gad gene maps to region 64A3-5 of chromosome 3L and encodes glutamic acid decarboxylase (GAD), the rate-limiting enzyme for the synthesis of the inhibitory neurotransmitter gamma-aminobutyric acid (GABA). Because this neurotransmitter has been implicated in developmental functions, we have begun to study the role of GABA synthesis during Drosophila embryogenesis. We show that Gad mRNA is expressed in a widespread pattern within the embryonic nervous system. Similarly, GAD-immunoreac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…2A) revealed that DACK is removed by the deficiency Df(3L)C175, mapping it to 64A3-64A5. The 64A region has been well characterized genetically and it is likely that most of the essential genes have been found (30,41). Five lethal complementation groups have been identified which are removed by Df(3L)C175, with all being represented by at least six alleles, except for l(3)64Am, which has one allele (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2A) revealed that DACK is removed by the deficiency Df(3L)C175, mapping it to 64A3-64A5. The 64A region has been well characterized genetically and it is likely that most of the essential genes have been found (30,41). Five lethal complementation groups have been identified which are removed by Df(3L)C175, with all being represented by at least six alleles, except for l(3)64Am, which has one allele (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the major components of GABAergic systems have been detected throughout most stages of Drosophila development by both immunocytochemical and molecular analyses. mRNA transcripts for glutamic acid decarboxylase (GAD), the synthetic enzyme for GABA, were detected in the CNS of embryos, larvae, pupae, and adults (Jackson et al, 1990) and a GAD-immunoreactive protein was also detected in neuronal tissues during embryogenesis (Kulkarni et al, 1994). Immunocytochemical analyses detected the Drosophila GABA receptor subunit Rdl in the CNS of embryos and throughout the adult brain as well as within the ellipsoid body of the adult CC (Aronstein and Ffrench-Constant, 1995;Harrison et al, 1996).…”
Section: Gaba Transporters Are Implicated In the Regulation Of Physiomentioning
confidence: 98%
“…1H; data not shown). Immunofluorescent and immunohistochemical stainings were performed as described by Patel (Patel, 1994), using the following antibodies: Guinea pig anti-Dbx (1:1500), rabbit anti-vGlut [1:5000 (Daniels et al, 2004)]; rabbit anti-Eve [1:3000 (Frasch et al, 1987)], rabbit and guinea pig anti-Hb9 (1:1500), rabbit anti-GAD [1:1000 (Kulkarni et al, 1994)], and rabbit anti-GFP (1:1000, Torey Pines). Monoclonal antibodies (obtained from the Developmental Studies Hybridoma Bank, Iowa): 9E10 (Myc 1:10,), 1D4 (FasII; 1:10), BP102 (1:10), 4D9 (engrailed/invected; 1:10), 7E8A10 (ELAV; 1:10).…”
Section: Antibody Production and Immunostainingmentioning
confidence: 99%